Preclinical Assessment of Paclitaxel- and Trastuzumab-Delivering Magnetic Nanoparticles Fe3O4 for Treatment and Imaging of HER2-Positive Breast Cancer - Guo, Liting; Zhang, Hongming; Liu, Ping; Mi, Tianai; Ha, Da; Su, Li; Huang, Lei; Shi, Yan; Zhang, Jun (Frontiers in Medicine, 2021)
Objective: The purpose of this study was to investigate the anticancer activity and the potential imaging use of the innovative combination of magnetic nanoparticles (MNPs)-Fe3O4, paclitaxel (PTX), and trastuzumab (Herceptin) in HER2-positive breast cancer. Methods: MNPs-Fe3O4 was synthesized and underwent water phase transfer and hydrophobic molecular loading, and its surface was then coupled with Herceptin mono-antibody. The morphological characteristics of MNPs-Fe3O4 were observed under transmission electron microscopy (TEM). Effects of PTX-Herceptin-MNPs-Fe3O4 on cancer cells were evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,4-diphenyltetrazolium bromide assay and the flow cytometric apoptosis assay. To establish a xenograft model, we injected breast cancer SK-BR-3 cells into the left thighs of nude mice. We measured the effect of PTX-Herceptin-MNPs-Fe3O4 on tumor growth by measuring tumor size and calculating inhibition rate with immunohistochemistry analysis further performed, and analyzed MNPs-Fe3O4 accumulation in tumor lesions using in vivo magnetic resonance imaging and in vivo fluorescence imaging. Results: Most MNPs were in spherical shape of about 10 nm in diameter observed under TEM. PTX-Herceptin-MNPs-Fe3O4 induced a higher apoptosis rate of SK-BR-3 cells than PTX-Herceptin, with corresponding changes of apoptosis-related proteins. Meanwhile, the in vivo tumor xenograft model showed that tumor inhibition rate in the PTX-Herceptin-MNPs-Fe3O4 group was higher than in the PTX-Herceptin group. Furthermore, PTX-Herceptin-MNPs-Fe3O4 enhanced the T2 imaging contrast enhancement effect on tumors in tumor-bearing mice. Conclusion: The novel PTX-Herceptin-MNPs-Fe3O4 combination may represent a promising alternative breast cancer treatment strategy and may facilitate tumor imaging.